ANALISIS DAN IMPLEMENTASI MIKROTIK ROUTER BOARD RB450G UNTUK MANAJEMEN JARINGAN (STUDI KASUS : BADAN PENGKAJIAN DAN PENERAPAN TEKNOLOGI SUB BALAI BESAR TEKNOLOGI ENERGI (B2TE-BPPT) SERPONG) - Rahmat Rizkiyanto (Esensi: Jurnal Bisnis dan Manajemen, 2014)
The importance of a management of the network in B2TE and optimize use of existing network devices. During this time, the network system that is running can’t be managed properly. There are still problems, especially related to topology, traffic network system, bandwidth, access rights, and the login process. On the basis of these, carried out an analysis and implementation of development using Network Development Live Cycle (NDLC) with activity analysis, design, prototype simulation, implementation, monitoring, and management. Development method is applied to solve problems that occur. Data collection methods used are the methods of observation and interviews with the B2TE and do a similar study. To resolve issues related to topology, topology implemented using the router board. For traffic network system, load balancing system implemented by the method of Per Connection Classifier (PCC). Queue tree with Hierarcial Token Bucket (HTB) method and Per Connection Queue (PCQ) and hotspot system is applied to solve problems related to bandwidth and permissions. Single sign-on system (SSO) with Open LDAP and RADIUS functioned to minimize the use of username and password during the login process. From the test results of the implemented system, the selection router board it is appropriate to handle the problem topology. Load balancing with the PCC method, queue tree with HTB and PCQ methods and systems hotspot capable of answering traffic problems on the issue of network systems, bandwidth, and permissions. While the system SSO is capable of handling problems login process. For further development, it is expected that the system has been running for bandwidth management rule can be added to separate the local and international bandwidth. Then, for security, made ​​the policy in terms of access to the IP address and port. In terms of permissions, can be applied to the scheduling of access to certain sites. For the development of SSO, can be applied SSO system that can access multiple applications.DOI: 10.15408/ess.v4i1.1960